Rheumatoid arthritis and COVID-19: Three years later - B. S. Belov; E. S. Aronova; G. I. Gridneva; E. I. Nasonov (Научно-практическая ревматология)
During the three years that have passed since the beginning of the COVID-19 pandemic, many new fundamental and medical problems have been discovered regarding the relationship between the viral infection and many common chronic non- infectious diseases. Among the latter, an important position is occupied by immuno-inflammatory rheumatic diseases (IIRD), which include rheumatoid arthritis (RA). To date, there is no doubt that patients with RA are at risk for SARS-CoV-2 infection, a severe course of infection that necessitates hospitalization and death. The article presents current data on the course and outcomes of COVID-19 in patients with RA. The literature and own data on postcovid syndrome in this group of patients are presented. The necessity of vaccination against SARS-CoV-2 in patients with IIRD, including those with RA, was substantiated. The prospects for further study of the features of COVID-19 in patients with RA are outlined.